Human Resource Development and Civil Service (ASN) Competency Improvement as well as Government Governance within the Riau Province Regional Development Planning Agency (BAPPEDA) in 2024: Pengembangan Sumber Daya Manusia dan Peningkatan Kompetensi Aparatur Negeri Sipil (ASN) Serta Tata Kelola Pemerintah di Lingkup Badan Perencanaan Pembangunan Daerah (BAPPEDA) Provinsi Riau Tahun 2024 - Rais, Ermiyati (Jurnal Olahraga dan Kesehatan (ORKES), 2025)
Human resource development (HRD) and improving the competence of State Civil Apparatus are the keys to achieving effective and efficient governance. In BAPPEDA Riau Province, this effort is the main focus in facing regional development challenges. This study aims to analyze the strategy for developing State Civil Apparatus Human resources Development and its impact on government governance in 2024. The methods used in this study are literature studies and in-depth interviews with a number of officials at BAPPEDA Riau Province. The results show that planning, leadership support, educational cooperation and periodic evaluation in improving State Civil Apparatus competence through formal and informal training and education have a significant impact on the quality of public services and better decision-making In BAPPEDA Riau Province.